АРИДНОЕ ПОДНЯТИЕ КСУР В СЕВЕРНОЙ АФРИКЕ: ЭРОЗИОННАЯ И ДЕФЛЯЦИОННАЯ СКУЛЬПТУРА, КЛИМАТИЧЕСКОЕ И АНТРОПОГЕННОЕ ОПУСТЫНИВАНИЕ - Чичагов В.П. (My University, 2006)
The Ksur heights are situated between Great Eastern Erg and Gabes bay in the North Africa. The beginning of the tectonic uplift is dated to the Pliocene-Early Pleistocene, upward movements continued during the Pleistocene when erosion dissection took place. In the Holocene the Ksur heights underwent strong deflation. The new data on distribution of the Holocene eolian deposits in the North Africa and in the depression of Tunis shotts (the El'Garsa shott as an example) are discussed. Of seven Holocene layers of the El'Garsa shott five are eolain, which indicates long and intensive deflation within the Great Eastern Erg and western slope of Ksur heights. The questions of anthropogenic relief formation are discussed in details. Two stage of man-induced destruction may be distinguished: the epoch of Rome and the colonial period in the XX and XXI century. The impact of hostility may (in places) overpass the relief destruction during peace periods. The importance of war action for the arid regions destruction is emphasized.
Keywords: Кайнозой::Четвертичная::Голоцен; Кайнозой::Четвертичная::Плейстоцен; Кайнозой::Неоген::Плиоцен